CLINICAL, PARACLINICAL CHARACTERISTICS AND TREATMENT OUTCOMES OF INFLUENZA A IN CHILDREN UNDER 5 YEARS OLD AT THE HAI DUONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: This study to describe the clinical, paraclinical characteristics and evaluate the treatment outcomes of influenza A in children under 5 years of age treated at the pediatric department in Hai Duong General Hospital.Subjects: 40 children were diagnosed with influenza A and treated at the pediatric department in Hai Duong General Hospital from January 2025 to October 2025.Methods: A retrospective and prospective, cross-sectional descriptive.Results: the mean age of the study population was 34.2 ± 5.8 months, children aged from 12 to under 60 months were the most common, the male/female ratio was 1.86/1. The common clinical manifestation were fever (97.5%), cough (95%), and rhinorrhea (65%). Other symptoms such as headache, sore throat, myalgia, abdominal pain, vomiting were less common. The paraclinical showed that 50% of patients had leukocytosis and 15% had leukopenia, 55% of patients did not exhibit elevated CRP levels (
Keywords: influenza A, children, Hai Duong General Hospital.